A TWO-STAGE BI-LEVEL DECISION APPROACH FOR GREEN SUPPLY CHAIN DESIGN AND CLOUD VIRTUAL MACHINE PLACEMENT - Kao, Han-Ying; Lan, Zih-Heng; Huang, Chien-Hao; Huang, Chia-Hui (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
This study aims to establish an integrated model of green supply chain network design in cloud computing environments. In this study, two levels are defined: supply chain design and virtual machine allocation. In the proposed two-stage model, the supply chain network design decision (leader level) is solved in the first stage by considering three objectives: minimizing the total costs, minimizing the carbon emission, and maximizing the satisfaction level of service (minimizing the transportation lead time). In the second stage, considering the information demand from the leader level, the placement of virtual machines to the supply chain servers (follower level) is established by minimization of energy consumption and maximization of the effectiveness (minimization of the power wastage) of the physical machine. A case study and experiments are conducted to verify the performance of the proposed methods.